2022
DOI: 10.3389/fnut.2022.890730
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Dietary Fructose and Gut Microbiota in Hyperuricemia and Gout

Abstract: With the worldwide epidemics of hyperuricemia and associated gout, the diseases with purine metabolic disorders have become a serious threat to human public health. Accumulating evidence has shown that they have been linked to increased consumption of fructose in humans, we hereby made a timely review on the roles of fructose intake and the gut microbiota in regulating purine metabolism, together with the potential mechanisms by which excessive fructose intake contributes to hyperuricemia and gout. To this end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 177 publications
0
9
0
2
Order By: Relevance
“…In recent years, HUA has become a common metabolic disease worldwide [ 1 ], characterized by elevated levels of uric acid (UA) in the blood, which affects patients of all ages and genders [ 2 ]. Studies have shown that the global incidence of HUA has been on the rise since the 1960s, and up to 2016, the global incidence of HUA has been as high as 21% [ 1 ]. The incidence rate in the United States ranges from 14.6% to 20% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, HUA has become a common metabolic disease worldwide [ 1 ], characterized by elevated levels of uric acid (UA) in the blood, which affects patients of all ages and genders [ 2 ]. Studies have shown that the global incidence of HUA has been on the rise since the 1960s, and up to 2016, the global incidence of HUA has been as high as 21% [ 1 ]. The incidence rate in the United States ranges from 14.6% to 20% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research suggests that a diet rich in fructose also affects the immune system and may disturb the body’s immune homeostasis through, for example, changes in the intestinal bacterial flora and the impact on the permeability of the intestinal barrier. Attention is paid not only to the role of fructose itself, but also to the impact of its metabolites on the immune system [ 64 ] Fang et al [ 65 ] drew attention to the effect of fructose on the intestinal microflora and the possibility of fructose-inducing inflammation, which both contribute to the formation of hyperuricemia and disorders in intestinal homeostasis.…”
Section: Fructose As a Potential Factor Influencing Hyperuricemia And...mentioning
confidence: 99%
“…In addition, studies have shown that an excessive fructose diet can affect gut microbiota composition through a series of damage to the intestinal barrier function of the inflammatory response. Therefore, a new method for gout treatment could be to limit the specific fructose intake and improve the composition of gut microbiota or targeted metabolite ( Fang et al., 2022 ).…”
Section: Treatment Of Goutmentioning
confidence: 99%